Capital quality improvement and the sources of growth in the euro area - Plutarchos Sakellaris; Focco W. Vijselaar (Center for Economic Studies and ifo Institute (CESifo), 2005)
The euro area experienced a slowdown in output and Total Factor Productivity growth in the 1990s compared to the 1980s. We ask the following questions. Is the apparent slowdown in euro area output due to a lack of proper accounting for capital quality improvement? The answer is no. Did technological change really slow down in the euro area? The answer here is mixed. The part of the technological change that is embodied in capital goods and boosts output through investment in these goods in fact accelerated in the 1990s. In contrast, disembodied technological change, which boosts output through new consumer goods or new production processes, decelerated in the 1990s more sharply than the official figures portray.
Keywords: O47; O30; 330; Wirtschaftswachstum; Technischer Fortschritt; Gesamtwirtschaftliches Anlagevermögen; Preisindex; EU-Staaten